Economic policy uncertainty and earnings management: Evidence from Japan - Kim, Hyonok; Yasuda, Yukihiro (Journal of Financial Stability, 2021)
We empirically examine the effects of economic policy uncertainty (EPU) on earnings management in Japan. We find that EPU is negatively associated with earnings management, indicating that managers have incentive to reduce earnings management when EPU increases. We then examine the monitoring roles of various entities, focusing on the main bank that holds equity in their client firm. We find that the relationship between EPU and earnings management is less pronounced for firms with a main bank. The result is consistent with the view that the main bank’s monitoring role works well in normal times, resulting in less room for management to improve earnings quality when EPU is high. We find a similar result when considering firms with and without analyst coverage. These results suggest a moderating role of main banks and analysts in the relationship between EPU and earnings management. Finally, we find that the effect of EPU differs depending on subcategories on policy uncertainty and the extent of each firm’s exposure to that type of uncertainty.